Status of the phase-2 tracker upgrade of the CMS experiment at the HL-LHC - Calligaris, Luigi [UNESP] (IOP Publishing, 2020)
The Phase-2 Upgrade of the CMS experiment is designed to prepare its detectors for operations at the High Luminosity Large Hadron Collider (HL-LHC). The upgraded collider, scheduled to start operations in 2027, will lead to challenging conditions in terms of data throughput, pile-up and radiation. For these reasons the tracker detector will be entirely replaced by a new detector, the Phase-2 tracker. We present the status of the design, test and validation of the components of the Phase-2 tracker, and its read-out, calibration, control, and data processing chains.